Decreased monocyte shedding of the migration inhibitor soluble CD18 in alcoholic hepatitis. Issue 6 (June 2018) - Støy, Sidsel; Sandahl, Thomas Damgaard; Hansen, Anne Louise; Deleuran, Bent; Vorup‐Jensen, Thomas; Vilstrup, Hendrik; Kragstrup, Tue Wenzel
Abstract : Objectives: : During alcoholic hepatitis (AH) monocytes traverse the vascular boundaries and massively invade the liver. In principle, tissue extravasation can be limited through shedding of CD18 integrins from leukocytes, including monocytes. The soluble (s) product sCD18 conceals adhesion receptors on the endothelium, which reduces monocyte extravasation. In AH, monocytes are dysfunctional, but whether this involves their self‐generated anti‐migration is unknown. Our aim was, therefore, to investigate monocyte CD18 dynamics in AH. Methods: : We studied 50 AH patients and 20 healthy controls. We measured monocyte expression and conformational activation of CD18, plasma (P)‐sCD18, stimulated in vitro CD18 shedding and P‐sCD18 in a short‐term chronic‐binge mouse model. Results: : AH‐derived monocytes had a 30–60% higher expression of active CD18 receptors ( p < 0.01), but the sCD18 concentration per monocyte was reduced in vivo by 30% and in vitro by 120% ( p < 0.01). Ethanol reduced the in vitro shedding of CD18 in the patients only. TNFα increased sCD18 concentration per monocyte, but less so in the patients ( p < 0.04). P‐sCD18 per monocyte was inversely related to disease severity. In early alcoholic liver disease, P‐sCD18 was decreased in the mouse model. Conclusions: : The monocyte CD18 integrins are highly activated in AH and the single monocyte shedding of CD18 was decreased favoring tissue extravasation. Alcohol in itself and altered monocyte responsiveness to TNFα may explain this lowered shedding. Translational impact: : The contribution of this mechanism to the excessive monocyte liver infiltration in AH should be further explored as it may serve as a potential therapeutic target to limit liver inflammation.